Impact of Communication and Creative Elements of Banner Advertisements on Consumer Interaction. - Varun Dave, Manvi Chawla, Dr. Preetha Menon (International Journal of Advanced Science and Technology, 2020)
Advertisers many a time use several creative ele- ments in their online campaigns to target the consumers with convenience-based messages and price-based promotions. There are also multiple creative designs and formats to improve the online audience interaction and conversion. The aim of this paper is to study the impact of communication and creative elements on the spends, impressions and click-through rates of banner advertisements using data from live banner advertisements from Facebook channel. It uses an automatic image tagging tool to combine creative elements with Facebook metrics and helps in analyzing the performance of each element on audience interaction. The click-through rate of an ad has been the standard yardstick for evaluating the effectiveness of the ad. The ad spends and impressions together with the click through rates measures audience interaction. Communication elements evaluated include the use of Convenience, Pricing and promotions appeals. Design elements evaluated include the use of color and product type. The research methodology employed was a quantitative observation experiment and data was gathered from Facebook ads manager which the company used for digital promotions. The data of the past six months was collected. The analysis suggests that communication and creative elements differently for various audiences segmented on the basis of demographic variables such as age and gender. This data helps in uncovering actionable insights and making creative decisions better and faster. This study is a real experiment that helped an online rental company design the most effective banner advertisement and shape for their advertising goals